Learning Video Making Workshop: Computer-Based Learning in the Industrial Revolution 4.5 Era at PGRI Sodonghilir Tasikmalaya - Rahadian, Dian; Dadang, Dadang; Nurhayati, Fitri; Hidayat, Andi; Fatimah, Imas; Mariah, Dede; Febriyanti, Fitri Ayu; Kusnadi, Engkus; Lani, Lani (Indonesian Journal of Community Empowerment (IJCE), 2023)
Along with technological advancements, traditional learning faces challenges. In today's digital era, conventional learning, which relies solely on lectures, is no longer sufficient to motivate students. The community service approach used in the "Learning Video Making Workshop: Computer-Based Learning in the Industrial Revolution 4.0 Era" at PGRI Sodonghilir Tasikmalaya was designed to provide integrated, participatory, and contextual training to improve teachers' skills in creating instructional videos. The training method consisted of several stages tailored to the participants' needs and local conditions. The workshop was conducted in several stages, beginning with an orientation and needs assessment. In this session, participants were invited to explore the obstacles they face and opportunities in using technology in education. Evaluation results showed that most participants felt more confident and motivated to apply video-making techniques in their classrooms. The workshop also highlighted the importance of adequate infrastructure support, including access to technology and a stable internet connection, as prerequisites for the successful implementation of instructional videos.